A possible drug interaction between sodium valproate and clonazepam resulting in severe drowsiness and limb weakness：A case report and literature review - Meng, Xiaotong; Wang, Bo; Deng, Manqing (Serican Journal of Medicine, 2025)
The treatment process of an 11-year-old girl diagnosed with Angelman syndrome, who experienced severe drowsiness and limb weakness following the combination of sodium valproate and clonazepam, is analyzed herein. Initially, the patient was prescribed levetiracetam, clobazam, clonazepam, and sodium valproate. However, she subsequently developed significant lethargy and weakness in her limbs. Upon her admission, the clinical pharmacist take medication reconciliation the following day, identifying clonazepam as a highly relevant factor in her condition. The medical team collaboratively adjusted the inappropriate medications. Ultimately, the patient’s symptoms improved, leading to her discharge.